Manajemen Kinerja : Meningkatkan Competitive Advantage Pada Lembaga Pendidikan Islam - Aswaruddin Aswaruddin; Yuni Syafriani; Suci Ramadhani; Dawi Nurjannah; Yogi Andrian; Zainur Rozzaqiyah; Aldi Bayu Anggara (Pusat Riset dan Inovasi Nasional, 2024)
Entering the era of globalization , the Islamic educational institutions have a huge responsibility in responding to various demands of society , especially in improving the quality of education by improving the quality of human resources in it . Performance management is one of the alternatives that can be used by Islamic educational institutions to improve the quality of human resources in order to achieve its objective of institutional accordance with market demand. Through performance management applied to the Islamic education institutions, is expected to create a climate and atmosphere -oriented organization of quality (quality culture) and has keungulan compete ( competitive advantage) with other educational institutions